Pengaruh Media Interaktif Genially Berbantuan Model Discovery Learning terhadap Hasil Belajar Kognitif pada Materi Sistem Saraf Siswa Kelas XI SMA Negeri 5 Samarinda - Dinda Davanya; Sri Purwati; Sonja V. T. Lumowa; Suparno Putera Makkadafi; Nelda Anasthasia Serena (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effect of Genially interactive media supported by the discovery learning model on students' cognitive learning outcomes in the nervous system. This research is motivated by the low level of student active engagement in learning, necessitating innovative media and learning models that support meaningful conceptual understanding. This study used a quasi-experimental method. The subjects consisted of an experimental class using Genially media supported by the discovery learning model and a control class using the expository model. The study was conducted on eleventh-grade students of SMA Negeri 5 Samarinda on the nervous system. The research instrument was an essay test administered before and after the lesson. Data analysis included normality tests, homogeneity tests, hypothesis testing using the independent sample t-test, and N-gain calculations. The analysis results showed that the data were normally distributed and homogeneous. The hypothesis test revealed a significant difference between cognitive learning outcomes in the experimental and control classes. The improvement in cognitive learning outcomes in the experimental class was in the moderate category and higher than in the control class. Thus, Genially interactive media supported by the discovery learning model is effective in improving students' cognitive learning outcomes in the nervous system.